The fraud audit : responding to the risk of fraud in core business systems - Vona, Leonard W., 1955- 521790 (Hoboken, N.J. : Wiley, 2011)
"Essential guidance for creation of an effective fraud audit program in core business systems. The Association of Certified Fraud Examiners has reported that U.S. businesses lose up to $4 billion annually due to fraud and abuse. Discover fraud within your business before yours becomes another business fraud statistic. Fraud in the Core Business Systems provides a proven fraud methodology that allows auditors to discover fraud versus investigating it. Explains how to create a fraud audit program. Shows auditors how to locate fraud through the use of data mining. Focuses on a proven methodology that has actually detected fraudulent transactions. Take a look inside for essential guidance for fraud discovery within specific corporate F&A functions, such as disbursement, procurement, payroll, revenue misstatement, inventory, journal entries, and management override."--